2005
DOI: 10.4315/0362-028x-68.7.1457
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Salmonella Serovars, Escherichia coli O157:H7, and Staphylococcus aureus during Thawing of Whole Chicken and Retail Ground Beef Portions at 22 and 30°C

Abstract: Food regulatory agencies advise against thawing frozen meat and poultry at room temperature. In this study, whole chickens (1,670 g) and ground beef (453 and 1,359 g) were inoculated with Salmonella serovars, Escherichia coli O157:H7, and Staphylococcus aureus on the surface (all products) and in the center (ground beef). After freezing at Ϫ20ЊC for 24 h, products were thawed at 22 or 30ЊC for 9 h. Pathogen growth was predicted using product time and temperature data and growth values from the U.S. Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Type of data developed under constant conditions is to calculate cumulative before each temperature shift and then to apply the prediction of growth rate once cumulative has been exhausted (19). By using a primary model without to model pathogen growth, the latter calculation and its associated assumptions can be avoided.…”
Section: Table 3 Observed (O) Predicted (P) and Relative Error (Rementioning
confidence: 99%
“…Type of data developed under constant conditions is to calculate cumulative before each temperature shift and then to apply the prediction of growth rate once cumulative has been exhausted (19). By using a primary model without to model pathogen growth, the latter calculation and its associated assumptions can be avoided.…”
Section: Table 3 Observed (O) Predicted (P) and Relative Error (Rementioning
confidence: 99%
“…In addition, both S. aureus and E. coli O157:H7 that are sensitive to the antibacterial effects of levans, and Salmonella Typhimurium as well, have been frequently detected in raw and ground beef (Ingham et al ., ). Due to this, various intervention methods have been used to reduce these foodborne pathogenic bacteria in raw and processed beef, which involve chemical (Hajmeer et al ., ; Lim & Mustapha, , ) and physical treatments (Thayer & Boyd, ; Patel et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…This approach can highlight important violations, such failing to rapidly cool down large portions of food, and identify minor errors that are performed by most people but do not constitute significant risk, e.g., thawing meat or meat products at room temperature (56,76,109). Domestic food handling and food safety practices are complex actions that cannot be simplified into the two categories " right" or " wrong."…”
Section: Discussionmentioning
confidence: 99%
“…This point value is lower than that originally used by Worsfold and Griffith (109,110), who assigned 10 demerit points for the thawing of raw foods and storage of frozen foods. The demerit score for thawing raw meat and meat products was lowered based on the findings of Ingham et al (56) and Lianou and Koutsoumanis (76), who found that thawing whole chicken and retail ground beef at room temperature was not particularly hazardous. Lack of control or lack of knowledge of " use-by" dates was assigned 5 demerit points, as originally proposed by Worsfold and Griffith (109,110).…”
Section: Haccpmentioning
confidence: 99%